From the Mari archives : an anthology of old Babylonian letters - Sasson, Jack M. (Eisenbrauns, 2015)
"A selection of translations of the hundreds of letters from ancient Mari (Tell Hariri) on the Euphrates River, categorizing them by type of letter, contents, and with commentary on the ways in which the letters provide access into our understanding of ancient Mesopotamian society, in the 2nd millennium B.C.E."--Provided by publisher